Integrated weed management in kharif crops - Das, T. K.; Kaur, Ramanjit; Raj, Rishi (Indian Farming, 2016)
Weed dynamics occurs in crop fields across locations and over times. Several weed control options are available. No single method is sufficient for weed control permanently for a longer period. Herbicide is easier to apply, most efficient and cost-effective tool, but cannot be a sole and fool-proof strategy for weed management in crops and cropping systems. Therefore, integrated weed management, involving relevant and suitable weed control options applicable to crops or cropping systems and locations can be followed for controlling weeds effectively and economically.